Spiritualita umírajících pacientů - Prokop, Jiří, 1979- (2006)
The dissertation presented deals with the spirituality of the patient under terminal care. The topic has not been in the focus of concern in the Czech Republic. However, the persons caring for the dying should have a thorough knowledge of the spirituality, both as to the theoretical point of view and in terms of the practical skills. The method adopted is based on the interviews with patients. They provide impulses for the development of the theory and, vice versa, the theory is applied in the practical approach to patients. Categories of human dimensions are described from the theoretical point of view. Mutual interconnection is accented. The term of need used in the context of the spiritual service is considered reductionistic. The relation between pain and suffering is analyzed in the chapter dealing with pain. The human suffering is explored in terms of its sense in the human life. The question of the human dignity also has its place in the spirituality of dying people -- espec.